The patients knowledge about the role of calcium in the primary prevention of colorectal cancer - Wroński, Konrad; Bocian, Roman (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study : The objective of this research was to become aquainted with patients’ knowledge of the calcium role in the primary prevention of colorectal cancer. Material and methods : A group of 400 patients treated in Nikolay Pirogov Provincial Specialist Hospital in Łódź was interviewed by means of the author’s own survey in which specific tools were used to become aquainted with patients’ knowledge of the calcium role in the primary prevention of colorectal cancer. The necessary statistics were conducted by means of STATISTICA 7.1 and EXCEL 2008 programmes. Results: The analysis of the results shows that 363 (90.7%) of respondents did not know about the protective role of calcium in the digestive tract and reduce the risk of colorectal cancer. The study shows that 396 (99.0%) of respondents were not informed by doctors about the protective effect of calcium in the digestive tract. In this survey 357 (89.25%) of respondents did not know what is the recommended daily intake of calcium in the diet. Conclusions: The results of the study shows that patients do not know about the role of calcium in primary prevention of colorectal cancer and were not informed by their doctors about such action of calcium. Patients were not aware of the need to consume the Recommended Dietary Allowance of calcium in the diet, which shows little knowledge of the subjects on the diet. It seems necessary to change the eating habits of patients, while the introduction of nutrition education from an early age in the society. Such actions may prevent in the future many civilization diseases.